The long walk to freedom : runaway slave narratives - Carbado, Devon W.; Weise, Donald (Boston, Mass. : Beacon Press, 2012)
A compilation of 12 first-person accounts of the runaway slave phenomenon spanning eight decades. Told in the voices of the runaway slaves themselves, these narratives reveal the extraordinary and often innovative ways that these men and women sought freedom and demanded citizenship. Also included is an essay by UCLA history professor Brenda Stevenson that contextualizes these narratives, as well as a look into the daily life of a slave. Divided into four categories--running away for family, running inspired by religion, running by any means necessary, and running to be free-these stories are a testament to the indelible spirit of these remarkable survivors.
Keywords: Slave narratives -- United States; Fugitive slaves -- United States -- Biography; Slaves' writings, American; Slavery -- United States -- History -- 19th century -- Sources; Underground Railroad -- Sources